Dynamics classifications of extreme doubly stochastic quadratic operators on 2D simplex - Abdulghafor, Rawad Abdulkhaleq Abdulmolla; Shahidi, Farruh; Zeki, Akram M.; Turaev, Sherzod (Springer International Publishing, 2016)
We study the dynamics of extreme doubly stochastic quadratic operators (d.s.q.o.) on two dimensional (2D) simplex. We provide some examples of d.s.q.o. which have infinitely many fixed points. We prove that the trajectory of extreme d.s.q.o., starting at some interior point of the simplex is convergent. Finally, we classify the dynamics of all extreme points of d.s.q.o. on 2D.